Meretas Pola Hubungan Orang Tua Dan Anak dalam Membentuk dan Mengembangkan Karakter Anak - Titin Nurhidayati (FALASIFA : Jurnal Studi Keislaman, 2018)
Happy is the hope of every human being. Anyone wants their wishes, fromÂ birth to old age is reached. Various attempts were made to obtain these desires.Â Desire is very diverse and keeps changing from time to time. One of the desiresÂ of a normal human being is to have a peaceful family full of love and affectionÂ for sakinah-mawadah wa rohmah), accompanied by children who are prayingÂ and / or praying. And hope that someday their children can become leaders forÂ people, devote, benefit (to be the spreader of love = rahmatan lil â€˜alamin) toÂ the surroundings, and be fulfilled by Allah SWT with blessed property. As par-Â ents, they will definitely try to make their children become successful children.Â One of the basic capital of success is that children must have a successful ha-racter. The role of parents in the formation and character development ofÂ children from an early age is very important for later life. And exemplary has aÂ greater influence on children than advice and speech. A child needs a good ex-ample, and he takes an example from his parents. Therefore he has a tendencyÂ to imitate the behavior of people who are liked and try to appear like the per-Â son who is liked. In the formation and development of children's character, youÂ should use a religious approach because each religion leads to character forma-Â tion.